MORPHOLOGICAL EVOLUTION: ESTIMATION PRINCIPLES, PATTERNS, AND MECHANISMS - Vorobyeva E.I. (My University, 2006)
Directions, modes, specializations, and coordination systems of morphofunctional changes are discussed based on modern data. Phylogenetic heterochronies (pedomorphoses and outstripping), which provide the basis for parallel, mosaic, and saltation development and different rates of morphological evolution, are regarded as important events of morphological diversification. The analysis of specificity and relationships of structural levels of organization (including genetic and epigenetic) and the elaboration of evolutionary principles of their dynamic stability are thought to be the most promising fields of modern research. © Pleiades Publishing, Inc. 2006.
Keywords: EVOLUTIONARY MECHANISMS; EVOLUTIONARY PATTERNS; EVOLUTIONARY TRENDS; MORPHOLOGICAL EVOLUTION